Pengaruh Tata Letak Sistem Irigasi Tetes dan Jenis Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica Rapa var. Chinensis L.) - Nisa, Jamilatun; Romdhonah, Yayu; Rohmawati, Imas; Ritawati, Sri (Agriculture Faculty of Flores University, 2024)
Irrigation is the most important part of plant cultivation to meet the water needs for plant growth and yield. However, irrigation is a common problem in dryland areas. The drip irrigation system is an alternative to solve the problem of water droplets that can improve water use efficiency. One consideration when using drip irrigation is designing the irrigation layout so that the water supply to each plant is uniform. This study evaluated two layout layouts of drip irrigation systems for pok choi plants (Brassica rapa var. chinensis L.) with different planting media. The method used a split-plot design with 2 factors. Variation of drip irrigation system (V) was the main plot which consists of 2 levels, namely variation 1 (V1) and variation 2 (V2). Media type (M) served as a subplot comprised of 3 levels, namely soil (M0), soil+charcoal husk (M1), and soil+cocopeat (M2). The feasibility of these two drip irrigation system designs included drip discharge values, water uniformity coefficient, water distribution uniformity, and storage efficiency. Based on the evaluation of the feasibility of drip irrigation system design, design 1 (V1) gave better values for the average value of drip discharge (0.16 l/minute), uniformity coefficient (99.71%), uniformity of water supply (82.11%), and storage efficiency (73.89 %). The layout of the drip irrigation had a significant effect on the height of pok choi plants on 1 and 2 WAP.